Postinhibitory rebound neurons and networks are disrupted in retrovirus-induced spongiform neurodegeneration - Li, Ying (American Physiological Society, 2014)
Certain retroviruses induce progressive spongiform motor neuron disease with features resembling prion diseases and amyotrophic lateral sclerosis. With the neurovirulent murine leukemia virus (MLV) FrCasE, Env protein expression within glia leads to postsynaptic vacuolation, cellular effacement, and neuronal loss in the absence of neuroinflammation. To understand the physiological changes associated with MLV-induced spongiosis, and its neuronal specificity, we employed patch-clamp recordings and voltage-sensitive dye imaging in brain slices of the mouse inferior colliculus (IC), a midbrain nucleus that undergoes extensive spongiosis. IC neurons characterized by postinhibitory rebound firing (PIR) were selectively affected in FrCasE-infected mice. Coincident with Env expression in microglia and in glia characterized by NG2 proteoglycan expression (NG2 cells), rebound neurons (RNs) lost PIR, became hyperexcitable, and were reduced in number. PIR loss and hyperexcitability were reversed by raising internal calcium buffer concentrations in RNs. PIR-initiated rhythmic circuits were disrupted, and spontaneous synchronized bursting and prolonged depolarizations were widespread. Other IC neuron cell types and circuits within the same degenerative environment were unaffected. Antagonists of NMDA and/or AMPA receptors reduced burst firing in the IC but did not affect prolonged depolarizations. Antagonists of L-type calcium channels abolished both bursts and slow depolarizations. IC infection by the nonneurovirulent isogenic virus Friend 57E (Fr57E), whose Env protein is structurally similar to FrCasE, showed no RN hyperactivity or cell loss; however, PIR latency increased. These findings suggest that spongiform neurodegeneration arises from the unique excitability of RNs, their local regulation by glia, and the disruption of this relationship by glial expression of abnormal protein.